An Empirical Dayglow Model for the Lyman‐Birge‐Hopfield‐Long Band Derived From the Polar Ultraviolet Imager Data. Issue 8 (21st August 2018) - Wang, Lingmin; Luan, Xiaoli; Lei, Jiuhou; Dou, Xiankang
Abstract: The Lyman‐Birge‐Hopfield‐long band dayglow emissions near 1, 700 Å, which were observed by the ultraviolet imager on board Polar satellite, are characterized as a cosine‐like function of the solar zenith angle. These emissions are mainly excited by the solar extreme ultraviolet produced photoelectrons acting on the nitrogen molecules. The amplitude and phase factors are used to quantify the cosine‐like function and subsequently develop a dayglow model. In this study, a model is developed by considering broader dayglow emission areas outside the auroral oval, as the dayglow intensities in the dayside can exceed the auroral brightness, especially in summer. Also, this model is constructed by considering the seasonal variations of the two factors. It is demonstrated that, besides the strong solar cycle and universal time dependencies, the amplitude factors of the cosine‐like function show prominent seasonal variations, which are associated with the solar zenith angle changes. The amplitude factors are the largest in summer and smallest in winter. In addition, the dayglow phase factors show nearly constant values within each season, but throughout the year, they are higher in summer and equinoctial months and lower in winter. The dayglow model can benefit the investigation of global auroral patterns for all seasons. Key Points: More accurate variations of dayside dayglow with SZA are captured by considering both the low‐ and high‐latitude edges of the auroral oval The seasonal and diurnal variations of dayglow are found to be well associated with the SZA, which are considered in the empirical model Much improved dayside aurora than previous works are obtained in summer when the empirical model are applied